Perspectives on the Islamic Welfare State: The Goals of Economic Development Justice - Md. Abu Sayem; Naerul Edwin Kiky Aprianto; Adam Voak (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri Purwokerto, 2023)
The concept of The Welfare State, as developed in many Western countries, has proved to be an excellent program for earmarking economic resources for programs concerned with the welfare of the common people. Notwithstanding this successful developmental process however, the practical function of a Welfare State created in this way can allow the parallel functioning of actions that are not necessarily in the best interests of the general public. This article explores the nature of an alternative arrangement, that we term The Islamic Welfare State, which is built upon a range of spiritually consistent concepts to realize its developmental and social welfare goals. In this regard, following the arguments and descriptions available in the literature, our review indicates that the Western and Islamic Welfare States are largely not compatible. Whereas the Western model focuses mainly upon economic issues, the Islamic Welfare State seeks to more efficiently deal with society’s scarce resources, and ensure natural justice by focusing on the individual, showing particular concern for their material, moral and spiritual enhancement. We note that, although the concept of an Islamic Welfare State has not been thoroughly tested in practice, the underpinning concepts and philosophy can nevertheless be used to formulate current Government policies to improve society's welfare responsibilities. It is important to recognise that the Islamic Welfare State has a clear and worthy goal, namely the fulfillment and maintenance of Sharia objectives (Maqâsid Sharia) until finally, Falah is created as a parameter of their successful development